PENGALAMAN PERAWAT STRUKTURAL DALAM MENGHADAPI PANDEMI COVID-19 PADA INSTALASI GAWAT DARURAT RUMAH SAKIT RUJUKAN COVID-19 DI BALI - Juniartha, I Gusti Ngurah; Yanti, Ni Putu Emy Darma (Coping: Community of Publishing in Nursing, 2023)
Nurses worked in the Emergency Room (ER) are health professionals who are vulnerable to experiencing stress, fatigue, and emotional changes, especially during the COVID-19 pandemic. In order to deal with those problems, besides acting as a leader of ER nurses, ER leader has an important role in reducing these negative symptoms. The aim of this study was to describe the experience of ER leaders in dealing with the COVID-19 pandemic in the Emergency Room of COVID-19 referral hospital in Bali. This is a qualitative study with the post-positivism approach with phenomenology method. This research was carried out for 4 months at five Emergency Rooms at the COVID-19 referral hospital in Bali. Participants were selected using a purposive sampling technique and data collection was carried out using a semi-structured interview technique/in depth-interview on 8 participants consist of ER leaders and deputies. The results of the verbatim analysis in this study identified four main themes, namely: Caring for COVID-19 patients in the ER, Management of ER services during a pandemic, Solidarity with the ER team, Effective communication in the ER. The results of the study also show that during the COVID-19 pandemic, there were changes in service management that were adjusted to the applicable rules and policies from the management of the COVID-19 referral hospital. These changes make structural nurses have to be able to adapt and set an example to their team in providing services in extraordinary situations. To maintain the solidarity of the service team, the ER leaders must become a role model for motivating their team members in the ER by maintaining effective communication.